Public perception toward residential solar panels in Bahrain - Maha Alsabbagh (Energy Reports, 2019)
In 2017, Bahrain's Cabinet endorsed the country's first national renewable energy action plan. The plan included the installation of residential solar photovoltaic cells as a means of using renewable energy in government-built housing units. This was followed by the establishment of the country's first photovoltaic~solar panel~manufacturing~company and the introduction of a net metering policy. However, public acceptance of residential solar panels has not been researched. This study aimed to address this gap through the distribution of an online survey. A total of 764 complete responses were received. The results showed a considerable number of respondents were interested in installing solar panels. However, the respondents recognized several challenges in both buying and installing them, including capital cost, lack of information, and maintenance requirements. This study's findings offer insights on how the public perceives solar panels, along with issues the government needs to address to ensure successful public participation in the use of solar energy in the residential sector in Bahrain.
Keywords: 330; Climate change; Public acceptance; Solar panels; Survey; Willingness to pay